(3GdGSJjYGH aj eYQaI GdCUMGHs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s
(3ChdgG (B:s
(3HGH GdCaQGO ai GdTjf , TeGS Hf YKfGf Hf GdTQjO GdeNRhei s
(3BNQgG (B:s
(3bGd CHh YeQ QVi Gddg Yfg (B: (3agPG eG GfJgi EdjfG ef GdCSeGA hGdcfi ai GdQLGd hGdfSGA (B,(3bO LGAJ CMGOjK (B[ (3hHYO Pdc hVYJ KeGfi hQbGJ (B_ (3NWC (B_ (3ef GdLRA GdKGdK ai JQGLe MQa GdYjf (B] s
(3GdfSNI HgG MhGTs
(3HMhGTi GdfSNI JYdjbGJ LjOIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdbGVi CMeO Hf eMeO RHGQI GdNGUI HUfYGA (B((3JGQjN (B307) s
Keywords: (3GdJGQjNs